Efektivitas LiveWorksheet Untuk Meningkatkan Kompetensi Matematika Siswa Selama Masa Pandemi Di SD Al Jannah - Zakirman Zakirman; Nesha Resty Aufiana (EDUKASI, 2023)
Online learning has its own challenges, especially for elementary school-age children. In online mathematics learning activities the teacher must present materials in the right pattern so that learning from home can run effectively and optimally. One of the creativity that can be done by the teacher is to modify the Student Worksheet (LKPD) which was previously manual to be online called a liveworksheet. The purpose of this study was to determine the effectiveness of live worksheets to improve students' mathematical competence during the pandemic at Al Jannah Elementary School. This type of research is quasi-experimental. Number of experimental classes (only one) and using comparison techniques before and after being given treatment. The population in this study were all students of SD Islam, Nature and Science Al Jannah and the sample involved was 22 students. The data collection instrument used was multiple choice questions in the form of an electronic test. To analyze the data using the normality test (Kolmogorov Smirnov), homogeneity test and paired sample t-test. Based on the results of data analysis, it can be seen that the sig 2. Tailed value is 0.022. The conclusion that can be drawn based on the results of this test is that there is a significant difference between before and after using the live worksheet.